EFFECTIVENESS OF LEGAL PROTECTION FOR LAND RIGHTS CERTIFICATE HOLDERS AGAINST UNLAWFUL THIRD-PARTY CLAIMS - Mohamad, Alwi Rany; Djaja, Benny (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Legal protection for land rights certificate holders is a crucial aspect in realizing legal certainty in the agrarian sector. Land certificates, which are supposed to be the strongest evidence of ownership, still often face challenges in the form of claims from third parties that do not have a legal basis, such as oral inheritance claims, physical possession without certificates, or unrecorded customary recognition. This study aims to analyze the effectiveness of legal protection for land certificate holders in dealing with these claims. The method used is normative juridical with a case study approach, which examines national regulations such as the Law no. 5 of 1960 concerning Basic Agrarian Principles (UUPA) and Government Regulation No. 24 of 1997 concerning Land Registration as well as a number of court decisions, including cases involving unilateral cancellation of certificates. The results of the study show that although legal norms have provided strong protection through the principle of legality and the principle of legal certainty, in practice there are still gaps such as weak integration of land data, administrative inconsistency, and low public legal literacy. In addition, judicial practices are also not completely consistent in deciding land cases. Therefore, legal protection for land certificate holders has not been fully effective. It is necessary to strengthen the administrative system, strict law enforcement against claims without legal basis, and increase public understanding of the importance of formal legality in land transactions and ownership. With this step, it is hoped that Indonesia's land system will be able to provide substantive protection and prevent future agrarian disputes.